Deformation of face-centered cubic polycrystal and stress tensor components in grains; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Kiseleva S. Svetlana; Gibert I. Ivan; Popova N. Natalya; Koneva N. Nina (Materials structure and properties under modification, 2016)
Title screen